2020
DOI: 10.1039/c9tc05427h
|View full text |Cite
|
Sign up to set email alerts
|

Responsivity improvement of a packaged ZnMgO solar blind ultraviolet photodetector via a sealing treatment of silica gel

Abstract: A packaged high performance ZnMgO solar-blind UV photodetector is prepared via a silica gel sealing treatment. The responsivity and stability of the device is improved according to this sealing treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Solar‐blind ultraviolet (SBUV) photodetectors have broad application prospects in military and civil fields such as missile warning, space security communications, environmental monitoring, and fire monitoring due to their low background noise, high sensitivity, and strong anti‐jamming ability. [ 1–3 ] In recent years, owing to the unique advantages of all‐solid state, small size, intrinsic solar blindness, high thermal and chemical stability, strong radiation resistance, and low energy consumption, SBUV photodetectors fabricated from wide‐bandgap semiconductors including AlGaN, [ 4–7 ] Ga 2 O 3 [ 8–13 ] and ZnMgO, [ 14–16 ] have attracted significant attention and are generally considered to be the next generation of UV photodetectors. However, the preparation of high‐quality AlGaN with high Al composition suitable for solar‐blind detection still faces many challenges due to the significant lattice and thermal mismatches between the AlGaN layer and the hetero‐substrate and the high surface migration barrier of Al atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Solar‐blind ultraviolet (SBUV) photodetectors have broad application prospects in military and civil fields such as missile warning, space security communications, environmental monitoring, and fire monitoring due to their low background noise, high sensitivity, and strong anti‐jamming ability. [ 1–3 ] In recent years, owing to the unique advantages of all‐solid state, small size, intrinsic solar blindness, high thermal and chemical stability, strong radiation resistance, and low energy consumption, SBUV photodetectors fabricated from wide‐bandgap semiconductors including AlGaN, [ 4–7 ] Ga 2 O 3 [ 8–13 ] and ZnMgO, [ 14–16 ] have attracted significant attention and are generally considered to be the next generation of UV photodetectors. However, the preparation of high‐quality AlGaN with high Al composition suitable for solar‐blind detection still faces many challenges due to the significant lattice and thermal mismatches between the AlGaN layer and the hetero‐substrate and the high surface migration barrier of Al atoms.…”
Section: Introductionmentioning
confidence: 99%
“…25 Low- mismatch photodetectors have been reported in many literatures. 26–36 A lattice matched heterojunction is the basis for building high-performance semiconductor devices. Therefore, how to deposit a high-quality CuBr semiconductor film is of great research value.…”
Section: Introductionmentioning
confidence: 99%
“…With the research of the third-generation semiconductors, solar-blind ultraviolet photodetectors have attracted great attention due to their indispensable characteristics in the military field, environmental monitoring, medical imaging, security communication, high-temperature event monitoring, space observation, antiterrorism, security, and self-organizing network communication. Previous studies have shown that wide band gap semiconductors such as ZnO (3.37 eV) and GaN (3.4 eV) are promising candidates for constructing ultraviolet photodetectors with outstanding performance. However, for the absorption of solar-blind ultraviolet light, the band gap of the semiconductor material needs to be greater than 4.4 eV . As a new type of direct wide band gap semiconductor, Ga 2 O 3 has a band gap of about 4.9 eV, which is considered to be a suitable material for solar-blind ultraviolet photodetectors. , Ga 2 O 3 also has many advantages such as chemical and thermal stability, high saturated electron mobility, low growth cost, high breakdown electric field, low dielectric constant, and so on.…”
Section: Introductionmentioning
confidence: 99%